MAKNA SUNGAI DALAM RUANG HIDUP YANG BERUBAH: STUDI KASUS DAYAK NGAJU, KALIMANTAN TENGAH - Septi Dhanik Prastiwi (Handep: Jurnal Sejarah dan Budaya, 2021)
The rivers flow on the island of Borneo have had a significant function for human life since a long time ago. The river has had a role in the dynamics of civilization and environmental evolution in human life until now. With the construction of road infrastructure, the significance of rivers for riverside communities has also changed. This study sees how Ngaju people interpret the river in a living space that changes with development. The research was conducted in two villages which show the characteristics of different locations, society, and development rates. The villages are Talingke village on the bank of the Katingan River and Pangi Village on the bank of the Kahayan River. Data collection were through observation, interviews, and literature study. The study shows that the characteristics of the river area, the community, and the development rates affect the community in interpreting the river. On the one hand, Pangi people start to leave activities in the river, but they still hold the values of the river in their lives. On the other hand, Talingke’s people still focus their activities on the river but no longer have river values in their lives.